Business models for cloud computing: experiences from developing Modeling & Simulation as a Service applications in industry - Kiss, Tamas; Dagdeviren, Huseyin; Taylor, Simon J. E.; Anagnostou, Anastasia; Fantini, Nicola (Proceedings - Winter Simulation Conference, 2015)
The potential of cloud computing is gaining significant interest in Modeling & Simulation (M&S). The underlying concept of using computing power as a utility is very attractive to users that can access state-of- the-art hardware and software without capital investment. Moreover, the cloud computing characteristics of rapid elasticity and the ability to scale up or down according to workload make it very attractive to numerous applications including M&S. Research and development work typically focuses on the implementation of cloud-based systems supporting M&S as a Service (MSaaS). Such systems are typically composed of a supply chain of technology services. How is the payment collected from the enduser and distributed to the stakeholders in the supply chain? We discuss the business aspects of developing a cloud platform for various M&S applications. Business models from the perspectives of the stakeholders involved in providing and using MSaaS and cloud computing are investigated and presented.